The interactions of spontaneous abortion, dietary intake of selenium, and fat mass and obesity associated (FTO) genotype: a case-control study in Iran - Nooriani, Narjes; Saeedirad, Zahra; Shekari, Soheila; Nami, Sheyda; Mahmoudi, Zahra; Abbasi Mobarakeh, Khadijeh; Adabi, Somayyeh Bararnia; Khodarahmi, Shiva; Bahmani, Parsa; Doaei, Saeid; Ajami, Marjan; Gholamalizadeh, Maryam (Frontiers in Nutrition, 2024)
Background: Spontaneous abortion (SA) is reported to be associated with Fat Mass And Obesity-Associated FTO genotype and dietary intake of selenium. This research assessed the potential interactions between the risk of SA, dietary selenium intake, and the FTO rs9939609 polymorphism. Methods: This case-control study encompassed 192 women who experienced SA and 347 control participants. Dietary selenium intake was evaluated using a comprehensive food frequency questionnaire (FFQ) and Nutritionist IV software. The FTO gene was genotyped for rs9939609 polymorphism. Result: The findings showed that there were no significant variations in the case and control groups' dietary selenium intake. A lower selenium intake was inversely associated with SA only among individuals with the TT genotype of the FTO gene (β=-0.19, P=0.04). The results remained unchanged when age, BMI, physical activity, smoking, alcohol consumption, and calorie intake were taken into account. Conclusion: A link may exist between selenium consumption and SA, especially in individuals with the TT genotype in the FTO gene. These findings underline the influence of genetic factors on how dietary intake impacts SA. Further investigation is required to validate these conclusions